A aplicação da lei 10.639/03 no Currículo em Ação: o conteúdo de história do Ensino Fundamental I - Santos, Miriã Pereira dos (Universidade Estadual Paulista (Unesp), 2024)
O presente trabalho de conclusão de curso, teve como objetivo principal analisar os conteúdos de História e cultura africana, afro-brasileira e indígena presentes na apostila "Currículo em Ação", com enfoque no caderno de "Sociedade e Natureza" do aluno, responsável pelo conteúdo de história e geografia do Ensino Fundamental I. Verificando através uma análise documental, no material, se a obrigação estabelecida pela Lei 10.639/2003 e 11.645/2008 está sendo apresentada e trabalhada adequadamente. Partindo, portanto, de uma pesquisa qualitativa, será analisado o material do aluno "Currículo em Ação", que compõe os materiais de apoio para a implementação do Currículo Paulista, homologado pelo estado de São Paulo no ano de 2019.

The present undergraduate thesis aimed to analyze the contents of African, Afro-Brazilian, and indigenous history and culture present in the "Curriculum in Action" booklet, focusing on the student's "Society and Nature" notebook, responsible for the History and Geography content of Elementary School I. Through documentary analysis, it aimed to verify if the obligation established by Laws 10,639/2003 and 11,645/2008 is being presented and addressed appropriately in the material. Therefore, starting from qualitative research, the student material "Curriculum in Action," which constitutes the support materials for the implementation of the Paulista Curriculum, approved by the state of São Paulo in 2019, was analyzed.
The application of law 10.639/03 in the Curriculum in Action: the history content in elementary school education
Keywords: Ensino de história; Cultura africana; Cultura indígena; Lei 10.639/2003; Lei 11.645/2008; Currículo em ação; Racialização; Teaching of history; African culture; Indigenous culture; Law 10,639/2003; Law 11,645/2008; Curriculum in action; Racialization